Surgical Site Infection - Lubis, Aisyah; Wintoko, Risal; Ismunandar, Helmi; Windarti, Indri (Medula, 2024)
Surgical site infection (SSI) is a fairly common complication that can arise after surgery, both minor surgical procedures and more complex surgical procedures. This infection can occur due to the entry of pathogenic microorganisms into the surgical wound, causing an inflammatory reaction. This infection can prolong recovery time, increase mortality, require additional medical intervention, and affect the patient's quality of life. This impacts patient clinical outcomes as well as additional care costs. Factors such as surgical technique, cleanliness of the operating environment, use of implants, and the patient's health condition can influence and also contribute to increasing the risk of infection. Symptoms of surgical site infection include pain, swelling, redness, or the presence of pus in the surgical wound. When this infection occurs, immediate medical action is needed to prevent the spread of infection which can cause advanced conditions such as sepsis. Prevention of surgical site infections involves sterile measures before and during surgical procedures, the use of prophylactic antibiotics, and thorough post-operative monitoring. These efforts aim to reduce the risk of surgical site infections, ensure optimal recovery, and improve the overall results of the surgical procedure. An in-depth understanding of the risk factors and prevention of surgical site infections can help medical personnel provide quality care and ensure the success of the operation. There is also the importance of early detection and treatment of infections in patients undergoing surgery.